Fish distribution across altitudinal gradients in the Upper Paraguay River Basin: Implications for conservation in the Pantanal region - Adriana Maria Espinoza Fernando; Francisco Severo‐Neto; Fabiane Silva Ferreira; Lúcia Mateus; Karina K. Tondato‐Carvalho; Elaine Antoniassi Luiz Kashiwaqui; Heriberto Gimenes Junior; Wladimir M. Domingues; Carla Simone Pavanelli; Henrique Ledo Lopes Pinho; Jerry Penha; Yzel Rondon Súarez (Conservation Science and Practice, 2025)
Abstract Lack of sufficient knowledge of biological diversity is the first barrier to promoting scientifically‐based conservation policies in Neotropical regions, where high diversity and limited sampling remains a challenge. We compiled fish occurrences data from the whole Upper Paraguay River basin (UPRB) and evaluated the altitudinal variation in species richness, local contribution to beta diversity (LCBD) and composition. We also evaluate the influence of other environmental variables on species richness. Occurrence of a total of 342 native and five exotic fish species were recorded. Fish species richness was higher in lower portions of the basin, with a clear decrease from 400 m.a.s.l. Richness was negatively correlated with altitude, and positively correlated with net primary productivity and slope. The LCBD presented higher values on floodplain and in headwaters. Intermediate classes presented greater relative importance, as they present greater relative richness in a small relative area in the basin. We observed a partial overlap in species composition along altitude classes. Three species classified in some category of threat according to the conservation status of ichthyofauna in Brazil have a limited spatial extent of occurrence, restricted within the Serra da Bodoquena plateau. The obtained results highlight the unique diversity in the floodplain–plateau continuum, therefore, choosing protected areas must consider altitude gradients in the UPRB. Given the small area of the conservation units in the basin, the important role of higher altitude streams in regional fish species diversity and the several threats in the plateau, we conclude that an increase in conservation effort is needed in the plateau portion of the Upper Paraguay River basin.